Ocular and systemic features of sarcoidosis and correlation with the International Workshop for Ocular Sarcoidosis diagnostic criteria - Agrawal, Rupesh; Gonzalez-Lopez, Julio J; Meier, Fabio; Gupta, Bhaskar; Pavesio, Carlos E (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
Purpose: To describe the ocular and systemic features in biopsy proven (definite) and non-biopsy proven (clinical) ocular sarcoidosis and to compare the ocular features with those proposed by the International Workshop for Ocular Sarcoidosis (IWOS). Methods: Retrospective chart review of 83 patients who attended a tertiary referral uveitis clinic and were diagnosed with sarcoidosis. Patients were divided into two groups based on the type of diagnosis: those who had tissue biopsy confirmed diagnosis ‘definite sarcoidosis’ (n= 42; 50.60 %) and those who had ‘clinical sarcoidosis’ (n= 41; 49.40%). Ocular and systemic manifestations, including lung function tests and bronchoalveolar lavage findings were compared in the two groups. The ocular features were also compared with the categories laid down by the International Workshop on Ocular Sarcoidosis (IWOS). Results: The mean age at presentation was 38.75 years (SD=12.33), 55.42% patients were female and mean follow-up was 24.35 months (SD=18.35). Trabecular meshwork nodules and/or tent-shaped PAS (category II of IWOS) were observed more frequently in patients with biopsy proven sarcoidosis (26.19 % v/s 9.76%; p=0.08). After logistic regression analysis, the predictor coefficient curve showed area under curve of 0.7262. Lymphocytosis (38.61% and 28.02%, p=0.93) and monocytosis (55.11% and 53.83%, p=0.56) on bronchoalveolar lavage analysis was present in both the groups, highlighting presence of granulomatous disease. Conclusion: This study suggests high reliability for the clinical diagnosis of ocular sarcoidosis in patients with signs recommended by IWOS and that our diagnostic criteria are consistent with that of the IWOS.